Support for people with dementia experiencing severe responsive behaviours: Unpacking the disconnect between policy and practice. (24th January 2022) - Westera, Anita; Fildes, David; Bird, Sonia; Gordon, Rob; Samsa, Peter; Grootemaat, Pam
Abstract: Objective: The Severe Behaviour Response Team (SBRT) program, which was established in 2015 to support aged care residents with dementia experiencing very severe and extreme responsive behaviours received far fewer referrals than projected during its first year. This article describes the outcomes of a brief survey to identify potential barriers to referrals and identify opportunities to improve the uptake of the service. Methods: A pragmatic, quasi‐experimental study was conducted involving clinical leads working in a representative sample of care homes that had not used the SBRT. The study was part of the formative evaluation activities of an ongoing program evaluation. Results: Of the 53 clinical leads that participated in the survey, one‐third had not heard of the SBRT prior to being contacted. The remaining two‐thirds ( n  = 36) had not used the service due to the availability of existing resources and concerns regarding responsiveness of, and access to, the new service. Conclusions: Three themes emerged from the study relating to awareness of the service, responsiveness and the interface between local aged care and health services. Referrals increased following interventions to address the first two themes; however, they continue to remain well below the number projected. This indicates a fundamental disconnection between the policy design process and the day‐to‐day experience of residential aged care. The study highlights the importance of aged care clinical leads being engaged in dementia policy and program development processes to support improved targeting of resources.